Análise do desempenho térmico de um sistema de aquecimento solar utilizando coletor com superfície absorvedora em chapas de PVC - Reis, Edmilson Pedreira dos (2009)
It s presented a solar collector to be used in a system for heating bath water, whose main characteristic is its low cost. The collector consists of five plates of PVC with 10 mm thick, 200 mm in width and 1400mm in length, with an area equal to 1.4 square meters. The plates were connected in parallel to the ends of PVC tubes of  40 mm and 32 mm. The plates were coated on one side with aluminum sheets of soft drinks and beers cans open. The system worked on a thermosiphon and was tested in two configurations: the plates uncoated and coated with aluminum material, to determine the influence of material on the efficiency of the collector. For both configurations was used EPS plates below the surface to minimize heat losses from the botton. The thermal reservoir of the heating system is, also, alternative and low cost, since it was constructed from a polyethylene tank for storing water, with volume of 150 end 200 liters. It will be presented the thermal efficiency, heat loss, water temperature of the thermal reservoir at the end of the process and simulation of baths for a house with four residents. The will be demonstrated thermal, economic and material viability of the proposed collector, whose main innovation is the use of recyclables materials, cans of beer and soft drinks, to increase the temperature of the absorber plate.